Sequence analysis and characterisation of virally induced viperin in the saltwater crocodile (Crocodylus porosus). Issue 1 (July 2015) - Milic, Natalie L.; Davis, Steven; Carr, Jillian M.; Isberg, Sally; Beard, Michael R.; Helbig, Karla J.
Highlights C. porosus viperin is the shortest viperin species cloned to date at 338 amino acids. C. porosus viperin localises to lipid droplets, most likely via its N-terminal amphipathic helix. C. porosus cells maintain the ability to respond to both dsRNA, dsDNA and infectious ssRNA +ve and –ve sense viruses. Dengue viral infection of mammalian cells is significantly restricted by C. porosus viperin.